Регуляция поведения в супружеской паре в период ожидания ребенка - Юлия Валерьевна Ковалева (Психология. Журнал Высшей школы экономики, 2011)
The author tests her hypothesis that the behaviour of expectant women differs depending on their husbands’ individuality. She analyses such variables as behavioural control, internality and attitudes towards the early family experience and observes their correlation in future parents. She demonstrates that during the pregnancy period the spouses mutually adapt their behaviour and that each of them tends to reproduce his or her parental style.